Spatio-temporal analysis of dholes (Cuon alpinus) in Khao Yai National Park, Thailand - NORASET KHOEWSREE; MANANYA PLA-ARD; RONGLARP SUKMASUANG; PAANWARIS PAANSRI; YUWALUK CHANACHAI; BUNYATIPORN KAEWDEE; PHANITSUPHA PHENGTHONG (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Khoewsree N, Pla-ard M, Sukmasuang R, Paansri P, Chanachai Y, Kaewdee B, Phengthong P. 2022. Spatio-temporal analysis of dholes (Cuon alpinus) in Khao Yai National Park, Thailand. Biodiversitas 23: 2668-2678. The relationship of the occurrence of key wildlife species and other wildlife in the ecosystems is complex and unique as a result of interactions between species as well as responses to complex environments. Spatio-temporal analysis of dholes (Cuon alpinus) in Khao Yai National Park, Thailand, aimed to study of the coexistence of the dhole with its main prey, humans, and other physical factors based on camera trapping. The temporal and spatial overlap analysis found that dholes coexist with five prey species and also with humans. The dhole also occurred with a significant positive temporal or spatial overlap with 20 other potential prey species. It was found that water sources and villages had a negative effect on the dhole's occupancy while there was a positive effect from roads, elevation, and slope. The dhole's occupancy model was most closely related to small rodent proximity. It also was found that the dhole's occupation was also related to humans. Based on the results of this study, some recommendations were developed to advocate the strict management of recreation areas. There should also be a boundary between the area of ??human activities and the natural forest of the area and this should include the control of illegal entry into the area from the area surrounding the national park to reduce interactions between human activities and wildlife.